The Regulatory Framework of Digital Currencies in Malaysia: A Conceptual Paper - Teoh, Melissa Teng Tenk; Wong, Siew Chin; Yap, Angeline Kiew Heong; Saleh, Zakiah (European Publisher, 2019)
Malaysian regulators have recently published policy regulations for digital currency exchange that operate in the country, which are primarily intended to safeguard against money laundering and the risk of terrorism financing. Notably, previous theoretical and empirical studies have been conducted to explore the government governance on digital currency. However, development of regulatory framework of digital currency in Malaysian context is still lacking in many ways. The current study is based on the former foresight research results and literature review. It highlights the perception of regulators in the world, legal status and taxation policies of digital currency in Malaysia. Thus, the study proposes a conceptual framework that suggests the variables of characteristics of digital currency, perceived security and perceptions of users are important to be considered in developing a conceptual regulatory framework in Malaysian perspectives. The regulator(s) may gain insights of the degree of acceptance of digital currencies and the regulatory frameworks among Malaysians. The development of conceptual regulatory framework will shed insights on designing strategies to achieve an effective and robust Anti-Money Laundering and Counter Financing of Terrorism (AML/CFT) control measures associated with the use of digital currency. Such measures will be critical in safeguarding the safety and integrity of the financial system, and in promoting greater transparency in the conduct of digital currency transactions among current and potential investors.